Dietary antioxidant index and hypertension in the Iranian population: a nested case–control study within the Fasa adults cohort study - Firooznia, Mohammad amin; Rahimlou, Mehran; Sekhavati, Eghbal; Motazedian, Mohammadreza; Tabrizi, Reza (Frontiers in Nutrition, 2024)
 Lifestyle interventions, including dietary adjustments, have shown promise in managing hypertension.  Oxidative stress is a key factor in hypertension, and antioxidants from diets can help counteract its effects.  Previous research indicates an association between higher dietary antioxidant intake and a lower risk of hypertension development. This study demonstrates a significant inverse relationship between Dietary Antioxidant Index (DAI) and hypertension risk among the adults cohort population.  Higher DAI values are associated to a decreased risk of hypertension, highlighting the potential benefits of antioxidant-rich diets in hypertension prevention.  The findings emphasize the importance of including antioxidant-rich foods in dietary patterns as a complementary strategy for hypertension management.